AFK: reclaiming the holy through art - Torgeir Fjeld (Inscriptions, 2020)
Answering to the claim that our contemporary era has lost a connection to the domain of the sacred René Girard held that, contra Sigmund Freud, the myth of Oedipus was not primarily a story of patricide, but a hidden narrative of victimisation and expulsion. As an arch-example of mob logic the myth and Sophocles' play serve to gloss over a brutal and ritualistic sacrifice by claiming that it was the victim who acted in violation of the law; according to Girard the charges against king Oedipus were retroactively invented to justify the initial act of expulsion. In the street-art of AFK we encounter images that activate feelings of persecution and exile, uncovering a possible path to regain our connection to the holy.